Study of Methane Emission and Energy Efficiency in Adult Cross-bred Cattle and Buffaloes on Maintenance Ration - Das, Pallabi; Devalia, Bharat R.; Pandya, Paresh R.; Sorathiya, Kalpesh K.; Chaudhary, a, Mosam N.; Lunagariya, Pravin M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was planned to determine methane production and energy efficiency in cross bred cattle and buffaloes at maintenance on awheat straw-based total mixed ration. The experiment was conducted in two groups consisting of seven crossbred cattle (T1) and seven buffaloes (T2) with an average body weight of 395.04 ± 44.18 and 401.43 ± 13.26 Kg, respectively. Intake of gross energy, digestible energy, and metabolizable energy (Mcal/day)of cattle (T1) was lower (p >0.05) than buffaloes T2). Methane energy loss, when expressed daily and about percent of gross energy, digestible energy and metabolizable energy did not differ significantly. In conclusion, methane emission was non significantly (P >0.05) lower and hence energy efficiency was higher in crossbred cattle than buffaloes on wheatstraw-based total mixed maintenance ration.
Keywords: Buffaloes; Cattle; Energy efficiency; Methane emission.